Soil Loss as a Negative Externality in the Emergy Accounting: Case Study of an Agricultural Commodities Municipality in the Brazilian Savannah - Buller, Luz Selene; Bayma-Silva, Gustavo; Ortega, Enrique; Bergier, Ivan (Journal of Environmental Accounting and Management, 2026)
Brazilian agriculture has become prominent in the world in the last decades, especially by virtue of the expansion of agricultural commodities in the Cerrado biome with about 204 million of hectares in the central part of the country. From the 1960’s, the Cerrado has been occupied by migrants from southern Brazil who have converted the native vegetation (mostly woody savannas) into extensive pastures and monocrops. From coffee and cotton in the initial Cerrado’s agricultural occupation to soybean, corn, cattle and swine nowadays, the landscape suffered a huge transformation and several liabilities related to ecosystem services loss are emerging. São Gabriel do Oeste is a typical agricultural municipality of the Cerrado and, therefore, can be considered as representative of the current agricultural model. Along with climate change impacts of the conventional agriculture through greenhouse gas emissions, soil loss is worrying because it is not truly renewable if incorrectly managed. The emergy assessment of the agricultural system, including soil loss as a nonrenewable flow, was compared to the assessment including soil loss as a negative externality to better understand its impact on the emergy indicators. Soil loss and GHG emissions accounts for 95% of the total externalities and soil loss alone, for 46%. Moreover, different levels of soil loss were accounted for to infer its impact on the productive and economic systems. In addition, to conclude the assessment, the native forest area to compensate the dependence of the system on economy resources was calculated. The additional native vegetation area reaches 61% of the municipality area and the cost to the native forestry recovery is estimated in 1,039 EM$.ha-1·year-1. The results here presented can be useful for new agricultural public policies related to the ecosystem services compensation and payment mechanisms taking into account the extent and magnitude of ecosystem services loss.